Sécurité et politiques de l’Arctique : une perspective groenlandaise - Harhoff, Frederick (Études internationales, 1989)
The development through the past two decades has shown increasing military and political tensions in, and a corresponding military structuralization of the Arctic, partly because of the fact that Arctic waters of both super-powers are geographically adjacent in this region, and partly because new warfare technology, notably with nuclear powered and armed submarines, has facilitated advanced missile launching opportunities in Arctic waters. The article outlines the legal and political structure of the Greenland Home Rule and argues that the Home Rule should have a decisive say in security policy matters, since this may draw further attention towards the global environmental risks and disaster following from nuclear or chemical contamination and increase the pressure for a peaceful future in the Arctic.